PENGEMBANGAN WISATA JURANG PENGANTIN DI DESA RABA KECAMATAN WAWO KABUPATEN BIMA - Aris Munandar; Nafisah Nurulrahmatia; Nurhayati Nurhayati; Nurul Huda (Universitas Islam Malang, 2023)
This service aims to further introduce alternative tourist attractions in Raba Village, Wawo District, Bima Regency. Besides that, another goal of this service is to be able to increase the village's original income and provide jobs for the local village community. The methods used in this service activity are: socialization of the program, analysis of the attractiveness of tourist objects, environmental conditions and ease of access to tourist attractions, assistance and strengthening of human resources, assistance for institutional strengthening of tourism village community groups, assistance for participatory planning and development of tourist villages, and training and entrepreneurship assistance and making souvenirs to be sold at tourist sites. The result of the dedication is the formation of a natural tourist location